Epidemiologia da dengue em Vitória, ES, 1995-2009 - Cardoso, Ivana Macedo (2010)
Introduction: Vitória, the capital of Espírito Santo, is among the Brazilian municipalities with priority to control dengue. Despite the efforts of local government, the disease seems to be treading a path of relentless permanence and expansion. Objective: Thus, the epidemiological description of the disease in the city, characterizing its distribution in time, space and people, and the study of determinant factors of its incidence, imposes itself as an indispensable task in seeking more effective control measures. Methods: With delineation of a time-series ecological study, and relying in dengue cases reported to SINAN, describes the type of variation of dengue incidence in the city over a period of 15 years (1995 to 2009), analyzed by linear regression and seasonal average method; Taking the confirmed cases of dengue in the period of 2000 to 2009, it is characterized the profile of the ones affected by the disease; The meteorological data (temperature, precipitation and humidity) are correlated with dengue cases from 1995 to 2009; The Urban Quality Index of the 79 districts of the municipality in 2000, chosen as a socioeconomic status indicator, is correlated to the rate of cumulative incidence of dengue per district during 2000 to 2005; The level of infestation by the mosquito Aedes aegypti, measured by the House Índex, an indicator produced by the larval survey, is correlated with the total number of dengue cases, monthly, in the period of 1999 to 2009. The correlations are determined by using the Spearman correlation coefficient. Results: Dengue presented a pattern of seasonality and cyclical epidemic. Excluding the first epidemic (1995-1999), the incidence of the disease tended to increase. The proportion of dengue cases was highest among women aged 20 to 29 years, and similar between whites and African descent. There was a steady increase in children under 15 years, with statistical significance. The fatality rate was low. The correlation between climatic variables and dengue cases reported presented statistical significance with a time lag of 1 to 4 months. It was higher with temperature, followed by precipitation. The correlation between Urban Quality Index and the incidence of dengue did not present statistical significance. There was correlation between the House Índex produced by the Index Survey (LI) and the incidence of dengue, which did not occur with the house infestation rate generated through Rapid Assessment Index for Aedes aegypti (LIRAa). Conclusions: The sequential circulations of 11 serotypes DENV-2, DENV-1, DENV-3 and DENV-2, associated with the maintenance of high vector infestation were probably responsible for the maintenance of high dengue incidence in the city. The profile of the ones affected by the disease in the municipality is similar to those in Brazil. It was necessary to consider a time interval between the climatic data and the occurrence of dengue cases for the verification of more explicit associations. The Urban Quality Index was not a determinant factor in the incidence of dengue. The house infestation rate produced by LIRAa was not a good indicator of dengue epidemic risk in the city of Vitória in the analyzed period.